2018
DOI: 10.1007/s10661-018-6730-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of water shortage in Kabul River network on the plain areas of Khyber Pakhtunkhwa, Pakistan

Abstract: Kabul River is a shared resource of Pakistan and Afghanistan and is a major source of economy for both countries. It is used for irrigation, power generation, fishery, hunting, and recreation. This study explored human-induced impact on Kabul River and its associated wetlands. For an in-depth study, the area situated between the two tributaries of Kabul River, i.e., Shalam and Naguman Rivers, was selected. The focus of the study was to find out reduction in the wetland areas, its causes, and associated impacts… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…Nafees et al [69] reported that 68% of wetlands in Peshawar Basin has been converted to agricultural fields due to low flow in Kabul River. This study showed that high P-related pollution in river over last 30 years lead to eutrophication of wetlands [70] in the basin, and the local community convert these dry lands to agriculture fields that further increases pollution by escalating application of fertilizers.…”
Section: Discussionmentioning
confidence: 99%
“…Nafees et al [69] reported that 68% of wetlands in Peshawar Basin has been converted to agricultural fields due to low flow in Kabul River. This study showed that high P-related pollution in river over last 30 years lead to eutrophication of wetlands [70] in the basin, and the local community convert these dry lands to agriculture fields that further increases pollution by escalating application of fertilizers.…”
Section: Discussionmentioning
confidence: 99%
“…The Kabul River originates in Afghanistan and enters the territory of Pakistan through the Khyber District. The Kabul River, part of the greater Indus River watershed, is the chief source of water for aquaculture and agricultural irrigation in Khyber Pakhtunkhwa Province (Nafees et al, 2018). The Swat River, a major tributary of the Kabul River, is particularly critical for sustaining river‐based tourism, irrigated agriculture, hydropower, fisheries, and fishing communities; however, it also receives pollution from industries, agriculture, and domestic sources (Mohammad, 2018; Saving river Swat from growing pollution, 2007).…”
Section: Methodsmentioning
confidence: 99%
“…For example, limited access to clean water has contributed to human health concerns and economic challenges in Khyber Pakhtunkhwa Province in northwestern Pakistan (Fida et al, 2022; Miletto et al, 2021). In particular, poor water quality has been cited as a contributing factor to regional fish declines in the Swat and Kabul rivers, which are essential water sources to Khyber Pakhtunkhwa Province (M. Ahmad et al, 2010; Hayat Khattak et al, 2015; Ishaq et al, 2014; Nafees et al, 2018; Yousafzai et al, 2015). These fish declines have been linked to adverse impacts to the livelihoods and businesses of locals (Mohammad et al, 2011; Nixon, Ma, Zanotti, et al, 2022).…”
Section: Introductionmentioning
confidence: 99%
“…Approximately 2.3% of the total KRB area is covered by glaciers [1]. The average annual precipitation in the KRB ranges from 200 mm in the lower elevation to 3000 mm in the HKH mountains [22,23]. Regions of Peshawar, Nowshera, and Charsaddah in Pakistan are mainly irrigated with Kabul River water on 80.0%, 47.4%, and 84.7% of its total irrigated land, respectively [14].…”
Section: Study Areamentioning
confidence: 99%